Penanaman Nilai-Nilai Religius Dalam Pendidikan Karakter Anak Usia Dini Di Tk Narwastu Noelbaki Kabupaten Kupang - Honi Miati F. Manu; Petrus Logo Radja; Retno Jeki Krisnadina Lopo (Early Childhood Education Development and Studies (ECEDS), 2025)
Instilling religious values is an improtant thing to do in an educational institution. Kindergarten (TK) plays a very important role because it is the basis for further education, where various values are still easy to instill in children’s personalities in vaious ways, for example children are taught good manners, good character and helping each other. The purpose of this study was to determine the instillation of religious values in early childhood character education at Narwastu Noelbaki Kindergarten. The method used in the study was using a qualitative descriptive research method. While for data collection using observation and interview methods. The data analysis techniques used in this study were data reduction, data presentation and drawing conclusions. The results of this study are that the instillation of religious values in early childhood character education at Narwastu Noelbaki Kindergarten has shown good development of religious attitudes even though there are still religious attitudes that need to be taught continuously by teachers.